Text Book of Pediatric Gastroenterology Hepatology and Nutrition - Neopane, A; Rimal, S (Journal of Nepal Paediatric Society, 2015)
J Nepal Paediatr Soc 2014;34(3):254 DOI: http://dx.doi.org/10.3126/jnps.v34i3.12418